1994
DOI: 10.1093/oxfordjournals.eurheartj.a060481
|View full text |Cite
|
Sign up to set email alerts
|

Vascular injury following cardiac catheterization, coronary angiography, and coronary angioplasty

Abstract: All vascular injuries occurring at this hospital department over a 5-year period (1987-91) as a result of cardiac catheterization, coronary angiography, or coronary angioplasty (PTCA) and requiring transfusion, surgical consultation, or repair, are reviewed. Such complications may occur late and, to detect cases not apparent from the protocol accompanying every examination, a questionnaire was sent to all surgical clinics in the region asking for details of vascular surgical intervention after angiography. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
5

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 0 publications
2
31
0
5
Order By: Relevance
“…This is within the range of 0.05 % to 5.2% reported in literature [1,3,[9][10][11][12]. Most of these studies were performed retrospectively, as was the current study, and only Habscheid et al [11] reported in a prospective study using duplex ultrasound the highest incidence of 5.2%.…”
Section: Discussionsupporting
confidence: 74%
“…This is within the range of 0.05 % to 5.2% reported in literature [1,3,[9][10][11][12]. Most of these studies were performed retrospectively, as was the current study, and only Habscheid et al [11] reported in a prospective study using duplex ultrasound the highest incidence of 5.2%.…”
Section: Discussionsupporting
confidence: 74%
“…are well documented (Fransson & Nylander 1994). Two previous patients with retinal branch artery occlusion after percutaneous transluminal coronary angioplasty (Bucci et al 1989, Dickens et al 1994) and after directional coronary atherectomy (Filatov et al 1995) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In one case report the site of bleeding was found to be the thymic branch of the right innominate artery. A mediastinal haematoma after cardiac catheterisation may occur from injury of the small vessels near the aortic arch, specially when the transradial approach is used [3][4][5]. Sanmartin et al report on their experience in 3369 cardiac catheterisations via the radial approach performed between 2001 and 2003 [6].…”
Section: Discussionmentioning
confidence: 99%